Emergency hospitalizations for adverse drug events in China: Clinical pharmacists' approach to assessment and categorization. Issue 5 (5th March 2021) - Zhang, Yuyi; Jin, Li; Zhang, Xiaogang; Bai, Rong; Chen, Danxia; Ma, Yabin; Zhai, Xiaobo
Abstract: Purpose: Little is known about emergency hospitalizations owing to adverse drug events (ADEs) in Chinese populations. The aim of this study was to identify the types and characteristics of ADEs as well as estimate the length of hospital stay and ADE‐related costs in a hospital emergency setting in China. Methods: This prospective study was conducted in the emergency department of our hospital from April 1, 2017 to December 31, 2019. ADEs of patients admitted to the emergency department were collected by a clinical pharmacist during daily pharmacy rounds. Results: Of 4020 cases admitted to the emergency department, 198 emergency ADE‐related hospitalizations (4.93%) were noted, which were classified into certain ( n = 0, 0%), probable ( n = 122, 61.6%), and possible ( n = 76, 38.4%). The ADE was serious in 93.9% of the 198 cases. Ten cases were fatal, and two cases were life‐threatening. More than 80% of the emergency ADE‐related hospitalization cases were of patients over 60 years. The pharmacological agents implicated in the hospitalizations were oral antiplatelet agents (20.7%), oral hypoglycemic agents (16.7%), insulin (11.1%), and antihypertensive agents (9.1%). The average length of ADE‐related hospital stay was 10 (7.0–14.0) days. ADE‐related costs ranged from $1684.68 to $4531.35 for each hospitalization. The length of ADE‐related hospital stay and associated costs were statistically significant. Most ADEs ( n = 146, 73.7%) were preventable. Conclusions: Most emergency ADE‐related hospitalizations in older adults resulted from lack of medication monitoring or inappropriate medication. Improved management of medicines by clinical pharmacists has the potential to reduce ADE‐related hospitalizations in older adults in China.